EDUKASI PENGAMBILAN KEPUTUSAN DAN PENGEMBANGAN ORGANISASI KARANG TARUNA DESA CILANGKARA - Rahman, Daffi; Amin Ash Shabah, Musyaffa; Rahmawati, Rafika (Universitas Islam 45 Bekasi, 2024)
Youth organisations are expected to play a strategic role in creating a prosperous social environment. However, along with changes in social, economic, and cultural dynamics, an in-depth understanding of the extent of the role of youth organizations in efforts to improve community welfare and play an active role in the surrounding environment in carrying out organisational activities and in the community in building together the progress of Cilangkara Village, Serang Baru Subdistrict, Bekasi Regency and improving community welfare refers to systematic efforts to improve the living conditions and living standards of a community. In addition, welfare improvement also includes social aspects, such as community participation in decision-making, women's empowerment, and environmental sustainability. It is a holistic effort, involving collaboration between the government, social institutions and the community itself to create favourable conditions and improve the overall quality of life. This service uses the method of educational socialisation in decision-making. The results of the service show a positive and effective impact that can both help and broaden the insights of the administrators and cadres of the cilangkara village youth group on how to make decisions and can increase solidarity and a sense of caring from each division or structural and can lead to new innovations and creativity that can develop the youth group organisation.